The Potential of Wild Mango Leaves from Sumatera as the Immunostimulant Agent - Fitmawati Fitmawati; Erwina Juliantari; Agus Saputra; Patar Sinaga; Rodesia Mustika Roza; Mayta Novaliza Isda (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Wild Mango from Sumatera is potentially new immunostimulant. It contains mangiferin, which is potentially become the immunostimulant candidate. This study aimed to prove the immunostimulatory effect of wild mango leaves extract on white rat peritoneum fluid induced by Staphylococcus aureus bacteria. The immunostimulatory effect was determined based on the activity and capacity of macrophage phagocytosis. This study used 54 male white rats about 130 g - 290 g. Based on the results,the highest phagocytosis activity of macrophage cells was found in ethanol extract of Mangga Hutan leaves dose 2 with a percentage of phagocytosis activity was 84%. The highest phagocytosis capacity of the macrophage cells was also found in ethanol extract of Mangga Hutan leaves dose 2 with an average phagocytic capacity of 171.67 from 50 active macrophages. Results of this study indicated that wild mango leaves from Sumatera has the potential immunostimulant activity. This indicates that the wild mango have the potential for therapeutic efficacy for the prevention of degenerative diseases caused by immune deficiencies.